RELEVANSI DIMENSI ETIKA SOSIAL DALAM INTERPRETASI AL-AZHAR OLEH HAMKA - Eska Hifdiyah Sahal; Asri Sulastri (Almarhalah: Jurnal Pendidikan Islam, 2023)
This study aims to identify the style of social ethics, referred to as Adab Ijtima'i, contained in Hamka's Al-Azhar commentary. In addition, this study also aims to show that Hamka's tafsir Al-Azhar is characterized by the Adab Ijtima'i approach. The method of interpretation referred to as al-Adab al-Ijtima'ī mainly aims to explain the social instructions given in the Qur'ān. Moreover, the aim is to address and resolve social issues by providing these guidelines in a clear and pragmatic manner that can be easily understood and implemented in daily life. The key element in understanding tafsir adab al-ijtima'i is the harmonious integration of Quranic teachings with people's life behaviors, traditions, and cultural frameworks. This integration facilitates the application of these principles in the problem-solving process. In tafsir al-Azhar, Hamka uses the tafsir adabi ijtima'i approach to examine and explain the verses of the Quran. These clues can be found in various interpretations, which include legal verses and lyric poems referred to as Kauniyah.